Rapamycin-encapsulated nanoparticle delivery in polycystic kidney disease mice - Shinobu Yamaguchi; Randee Sedaka; Chintan Kapadia; Jifeng Huang; Jung-Shan Hsu; Taylor F. Berryhill; Landon Wilson; Stephen Barnes; Caleb Lovelady; Yasin Oduk; Ryan M. Williams; Edgar A. Jaimes; et al. (Scientific Reports, 2024)
Abstract Rapamycin slows cystogenesis in murine models of polycystic kidney disease (PKD) but failed in clinical trials, potentially due to insufficient drug dosing. To improve drug efficiency without increasing dose, kidney-specific drug delivery may be used. Mesoscale nanoparticles (MNP) selectively target the proximal tubules in rodents. We explored whether MNPs can target cystic kidney tubules and whether rapamycin-encapsulated-MNPs (RapaMNPs) can slow cyst growth in Pkd1 knockout (KO) mice. MNP was intravenously administered in adult Pkd1KO mice. Serum and organs were harvested after 8, 24, 48 or 72 h to measure MNP localization, mTOR levels, and rapamycin concentration. Pkd1KO mice were then injected bi-weekly for 6 weeks with RapaMNP, rapamycin, or vehicle to determine drug efficacy on kidney cyst growth. Single MNP injections lead to kidney-preferential accumulation over other organs, specifically in tubules and cysts. Likewise, one RapaMNP injection resulted in higher drug delivery to the kidney compared to the liver, and displayed sustained mTOR inhibition. Bi-weekly injections with RapaMNP, rapamycin or vehicle for 6 weeks resulted in inconsistent mTOR inhibition and little change in cyst index, however. MNPs serve as an effective short-term, kidney-specific delivery system, but long-term RapaMNP failed to slow cyst progression in Pkd1KO mice.